Gastric cancer-derived exosomal let-7 g-5p mediated by SERPINE1 promotes macrophage M2 polarization and gastric cancer progression - Zhenzhen Ye; Jianfeng Yi; Xiangyan Jiang; Wengui Shi; Hao Xu; Hongtai Cao; Long Qin; Lixin Liu; Tianming Wang; Zhijian Ma; Zuoyi Jiao (Journal of Experimental & Clinical Cancer Research)
Highlights SERPINE1 mediates the transfer of cancer-derived exosomal let-7 g-5p to promote macrophage M2 polarization. Exosomal let-7 g-5p drives M2 polarization by downregulating SOCS7 and relieving its inhibition of STAT3 phosphorylation. SERPINE1 promotes the transcription of let-7 g-5p by activating the JAK2/STAT3 signaling pathway.